ISLAMIC SCHOLARS’ NETWORK IN SOUTH SULAWESI AT THE 20th CENTURY: A Note in Wajo and Soppeng - Hamzah Harun Al-Rasyid; Husnul Fahima Ilyas (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
This article discussed about the network of scholars in South Sulawesi concentrated in Wajo and Soppeng districts. This research was significant to reconstruct and introduce scholars at the local level who were almost publicized, even though they had dedicated themselves in creating, educating, and attacking the nation's children with adequate religious knowledge. The primary concerns of this study were: how was the formation of the Islamic scholars (Ulama)’s network in South Sulawesi, and what were the roles of the Ulama in the formation of the network? This study aimed at reconstructing the network of Ulama over the achipleago, South Sulawesi, and Middle Eastern during the twentieth century. The results of this study revealed that the Ulama’s network in South Sulawesi, especially Wajo and Soppeng, highly relied on the Haramain network. Haramain alumni had a major influence on the development of traditional Islamic education in the form of halaqah (traditional teaching). For example, the halaqah center was formed in the early twentieth century at Salemo, Ajjakang/Mangkoso, Cabalu, and Wajo. Especially in Wajo KH. Muhibuddin or populary known as Ambo Emme, the initiator who encouraged KH. As'ad from Mecca to visit Sengkang Wajo in 1928, to teach about the Islamic values through halaqah developed by Ambo Emme. Halaqah had been changed into MAI (now the Islamic Boarding School of Asadiyah) which had produced a number of known scholars in building the halaqah and pesantren networks in the South Sulawesi region. They are, for example, KH. Daud Ismail from Soppeng who formed the YASRIB Islamic University Soppeng, KH. Yunus Martan in MAI-Wajo, KH. Abdurrahman Ambo Dalle from Wajo at MAI Mangkoso (now DDI), KH. Abduh Pabbaja from Sidenreng Rappang in DDI Ujung Lare and PP Al-Furqan, KH. Abdul Kadir Khalid MA from Wajo established MDIA Bontoala, KH. Asyri in developing the Darul Arqam Gombara Islamic Boarding School and Darul Aman.